Resource Utilization and Environmental Sustainability in Nigeria: Array - Ola, Temitope Peter (Acta Universitatis Danubius. Administratio, 2020)
This paper examines the issues of resources utilisation and how that affects the environmental sustainability profile of Nigeria. The paper notes that Nigeria has a substantial amount of human and material resources while the way and manner the resources are managed influences environmental sustainability within the nation and at the world at large. It is observed that despite numerous policy measures human and material resources are continuously wasted in Nigeria even as the nation continues on a downward trend of poverty. The paper concludes that something drastic needs to be done about how Nigeria manages its resources if sustainability must be attained.